PENERAPAN PARADIGMA INTEGRASI-INTERKONEKSI DALAM PENINGKATAN MUTU LULUSAN - Syarnubi Syarnubi (PAI RAFAH, 2022)
The purpose of this study is to find out how the Integration-Interconnection Paradigm and the Application of the Integration-Interconnection Paradigm in Improving the Quality of Graduates at UIN Suanan Kalijaga Yogyakart. This research is a study that utilizes the type of library research. Library research is research that collects data by collecting data from various literature. The research approach utilized is a qualitative approach, which is research whose findings are not obtained through quantification procedures, statistical calculations, or other forms of ways that use numbers. Qualitative research is principally to understand the object under study in depth. The results of this research are emphasized on an objective description of the actual state of the object under study. The concept of interconnection integration of State Islamic University Sunan Kalijaga is as follows: The scientific center of UIN Sunan Kalijaga Yogyakarta is the Qur'an and al-Sunnah which are developed through the process of ijtihad using various approaches and methods. In the development of the UIN Sunan Kalijaga Curriculum which offers four domains of integration-interconnection, namely: philosophical, material, methodology, and strategy: 1) In the philosophical realm, a scientific discipline always depends on other disciplines; 2) The realm of material, can be applied through three models, pertaining to